2011
DOI: 10.1111/j.1746-1561.2010.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

What Works? Process Evaluation of a School-Based Fruit and Vegetable Distribution Program in Mississippi

Abstract: The program fit well within the school structure and could be an effective component of a multifaceted approach to enhancing child nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 12 publications
5
58
0
Order By: Relevance
“…However, effective results of these interventions are scarce. Furthermore, the majority of studies developed in school canteens are focused on fruit and vegetable consumption and not on plate waste reduction (15,27,30) . For this reason, our results will only be compared with those focusing on food waste.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, effective results of these interventions are scarce. Furthermore, the majority of studies developed in school canteens are focused on fruit and vegetable consumption and not on plate waste reduction (15,27,30) . For this reason, our results will only be compared with those focusing on food waste.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a school-based programme developed in Mississippi, the main objective of which was to increase fruit and vegetable consumption, involving teachers and school staff eating food items and being a role model resulted in a positive effect on children's intake (27) . Reducing plate waste depends on many factors and will require action by school administrators as well as teachers, school lunch managers and other staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 A number of evaluations about FFVP feasibility, acceptability, and influence indicated that the program was well implemented and well received by students and school staff. 27,28 Students participating in the FFVP were exposed to a large variety of F/V and the program improved students' knowledge, preference, and willingness to try different F/V. [27][28][29][30] In studies that measured F/V consumption, students in FFVP-participating schools increased consumption of fruits 29,31,32 and combined F/V.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions in schools are seen as an effective instrument for improving the F&V intake of children (Howerton et al, 2007;Potter et al, 2011), and the European Commission (EU) Agriculture Ministers agreed in November 2008 to introduce an EU School Fruit Scheme (SFS) to promote the consumption of F&V among European school children. In North Rhine-Westphalia (NRW), the largest federal state in Germany, the SFS has been in operation since March 2010.…”
Section: School-based Interventionsmentioning
confidence: 99%